2023
DOI: 10.3389/fnut.2023.1208375
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-1031T/C gene polymorphism as a predictor of malnutrition in patients with gastric cancer

Abstract: IntroductionMalnutrition is a complex clinical syndrome, the exact mechanism of which is yet not fully understood. Studies have found that malnutrition is associated with anorexia and inadequate intake, tumor depletion, leptin, tumor-induced metabolic abnormalities in the body, and catabolic factors produced by the tumor in the circulation and cytokines produced by the host immune system. Among these, single nucleotide polymorphisms (SNPs) are present in the gene encoding the pro-inflammatory cytokine TNF-α.Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Elevated serum TNF-α levels have been observed in OLP patients compared to healthy controls [ 11 ]. So far, several single nucleotide polymorphisms (SNPs) within the promoter sequence (-238, -244, -308, -376, -489, -575, -610, -851, -857, -863, -1031) of the TNF-α gene have been reported that affect transcriptional regulation and therefore susceptibility of different diseases [ 19 , 20 ]. The SNP that occurs in the regulatory position − 1031, the promoter of the TNF-α gene, is characterized by the substitution of cytosine for thymine [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum TNF-α levels have been observed in OLP patients compared to healthy controls [ 11 ]. So far, several single nucleotide polymorphisms (SNPs) within the promoter sequence (-238, -244, -308, -376, -489, -575, -610, -851, -857, -863, -1031) of the TNF-α gene have been reported that affect transcriptional regulation and therefore susceptibility of different diseases [ 19 , 20 ]. The SNP that occurs in the regulatory position − 1031, the promoter of the TNF-α gene, is characterized by the substitution of cytosine for thymine [ 21 ].…”
Section: Introductionmentioning
confidence: 99%